THE CURATOR-MUSEUM: APPEARANCE, CONSERVATION AND DISAPPEARANCE OF THE WORK OF ART (Palíndromo, 2018)
In the last four decades, a considerable amount of museal institutions with differing goals turned themselves to constituting narratives that aimed to propose a meaning to their collections and how they were displayed. The main hypothesis of this text is centered on the curator-museum as an institution capable of producing a particular Art History, not always articulating with this discipli-ne’s canon and more attentive to tactics and devices of a “curatorship culture”. To such an end, we seek to debate a set of actions-in-artwork that expressed by the curatorial culture, the existence of an artistic production deliberately created, transformed and extinguished for and within museological institutions.
Keywords: art museum; curatorship; immaterial art; collections